Exosomes: Biogenesis, Composition, Functions, and Their Role in Pre-metastatic Niche Formation - Patil, Anandrao Ashok; Rhee, Won Jong (Biotechnology and bioprocess engineering, 2019)
Exosomes are a subclass of extracellular vesicles that are released by normal or diseased cells. Exosomes are natural nanoparticles, contain natural cargo, including lipids, proteins, and nucleic acids, and are involved in intercellular communication. Exosomes are detected in the tumor microenvironment and participate in tumorigenesis by regulating angiogenesis, immunity, metastasis, and formation of pre-metastatic niches. This review mainly focuses on exosome biogenesis, composition, their biological and pathological functions, and roles in pre-metastatic niche formation.